PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBASIS AKTIVITAS METAKOGNISI TERHADAP KEMAMPUAN MEMECAHKAN MASALAH KELARUTAN DAN HASIL KALI KELARUTAN PADA SISWA KELAS XI SMA NEGERI 2 BANJARMASIN - Anggun Oktavia Adityas; Parham Saadi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2015)
Abstract. This study aims to determine the effect of PBL model of metacognition activity based in learning solubility equilibria and the solubility product in class XI SMAN 2 Banjarmasin. This research method is a quasi- experimental design with nonequivalent control group design. The population was a student of class XI IPA SMAN 2 Banjarmasin. Samples were taken by purposive sampling, and class XI IPA 1 as the experimental class and XI IPA 3 as the control class. Data collection techniques using problem-solving test, observation and inventory sheets. Based on the ANAVA test showed that there were significance effect of PBL model of metacognition activity based in learning solubility equilibria and the solubility product in class XI SMAN 2 Banjarmasin.Keywords: PBL, problem solving, and solubility equilibria and the solubility product.